Komparasi Ketimpangan Pembangunan Antara Provinsi Sumatera Utara Dan Provinsi Sumatera Barat - Novita Purba Tambak; Mike Triani (Media Riset Ekonomi Pembangunan (MedREP), 2025)
The problem of development inequality is a crucial issue in Indonesia. Development inequality is caused by differences in geographical conditions of a region such as regional characteristics, natural resource potential, human resources and uneven investment levels between regions. North Sumatra and West Sumatra are in one region, namely Sumatra Island, which is in the same national fiscal system but has a contrasting pattern of inequality. This study specifically discusses the comparison of regional inequality levels measured using the Williamson Index between North Sumatra and West Sumatra Provinces based on Regency/City data by looking at the influence and how large the comparison of Regional Expenditure, TPAK, Infrastructure, HDI and Economic Growth of the two regions. This study uses statistical analysis with a difference test (t-Test) using BPS data from 2019-2023. The results show that there are significant differences in Regional Expenditure, TPAK, Infrastructure, HDI and Economic Growth between North Sumatra and West Sumatra and significantly affect development inequality.